Positioning to win: Key position-based performance indicators in elite soccer - Praça, G. M.; Brandão, L. H. A.; Silva, G. D. O. S.; Oliveira, P. H. D. A.; Costa, V. T. D.; Pinheiro, G. S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This study aimed to compare position-based variables between winning, losing, and drawing teams and to identify which among these variables would better predict the goal difference in the 2021-2022 German Bundesliga. The dataset comprised 275 official games, monitored through a semi-automatic camera system. For each game, players` and ball`s positions were captured and exported in 10 Hz. Position-based variables comprised teams` length, width, length per width ratio (LPWratio), stretching index, and near-the-ball space control in both offensive and defensive phases, as well as in the first and the second halves. Data were compared between the game outcomes using a Generalized Linear Model. Results indicated that winning teams in the Bundesliga tend to approach the first half of the game by expanding the field during the offensive phase (evidenced by a higher offensive width and stretching index), pressing high during the defensive phase (manifested through a greater defensive length), and exerting control over the space in the second half by concentrating players near the ball (indicated by higher near-the-ball space control). Differences between halves indicate that teams must be able to adapt their tactics during the game to succeed in the competition.